PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI KB-TK PANGUDI LUHUR SANTO VALENTINUS - Gentry Hastuti; Sarah Andrianti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research was designed to determine how applying the demonstration method can enhance the learning motivation of Early Childhood Education (PAUD) students at KB-TK Pangudi Luhur Santo Valentinus Surakarta in the academic year 2022-2023. This study utilized Classroom Action Research (PTK), where the researcher acted as an observer while implementing the learning process in the classroom. The subjects of this research were the students of Class B (KB B) with an age range of 3-4 years, consisting of 23 children. The object of this study was the application of the demonstration method used to improve the student’s learning motivation. Data collection techniques included classroom observations and interviews with the respective classroom teacher. The research findings indicated an improvement in the student’s learning motivation, which fostered self-confidence, responsibility, discipline, critical thinking, courage, and the ability to have good social interactions.